Efficacy of First Line Systemic Chemotherapy and Multikinase Inhibitors in Advanced Hepatocellular Carcinoma: A Systematic Review and Network Meta-Analysis - Oranratnachai, Songporn; Rattanasiri, Sasivimol; Pooprasert, Anantaporn; Tansawet, Amarit; Reungwetwattana, Thanyanan; Attia, John; Thakkinstian, Ammarin (Frontiers in Oncology, 2021)
Background Hepatocellular carcinoma (HCC) is the third most fatal cancer, with a 5-year survival rate of 18%. Standard frontline-therapy is multikinase inhibitors (MKIs), but accessibility is still limited, particularly in developing countries. This network meta-analysis (NMA) aimed to compare the efficacy of usual chemotherapy vs MKIs. Method Randomised-controlled trials (RCTs) comparing any among chemotherapy vs MKIs in treatment-naïve patients with advanced HCCs were identified from MEDLINE and SCOPUS databases. Overall survival (OS) and progression-free survival (PFS) probabilities and times were extracted from Kaplan-Meier curves using Digitizer, and then converted to individual patient time-to-event data. A one-stage mixed-effect survival model was applied to estimate median OS and PFS. A two-stage NMA was applied for the overall response rate and adverse events (AEs) outcome. Results A total of 20 RCTs were eligible for NMA. Lenvatinib was the best treatment among single MKIs, with median OS and PFS of 9 and 6.3 months, without significant differences in AEs relative to other MKIs. Median OS and PFS were 0.70 (-0.42, 1.83) and 2.17 (1.41, 2.93) months longer with Lenvatinib than Sorafenib. Among chemotherapy agents, FOLFOX4 had the longest median OS and PFS at 7.9 and 4.3 months, respectively, without significant AEs compared to other chemotherapies. The combination of Sorafenib+Doxorubicin prolonged median OS and PFS to 12.7 and 6.3 months, respectively. Conclusion Use of the MKIs Lenvatinib or Sorafenib as first line systemic treatment for advanced HCC could be beneficial. However, FOLFOX4 might be the optimal choice in a developing country where the health-care budget is limited.